The Effect of Earnings Management, Profitability, and Capital Structure on Firm Value in Manufacturing Companies Listed on the IDX 2021-2023 - Fariqha Ulin Nuha; Zeni Rusmawati; Dedy Surahman (P3I UMSurabaya, 2025)
Manufacturing companies are companies that play an important role in the economy in Indonesia. It has an impact on increasing the company's value in a view of stakeholders and investors. This research aims to determine the influence of profit management, profitability (ROE) and capital structure (DER) on company value (PBV) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2021- 2023. This research is quantitative research with secondary data obtained from the company’s annual report. The population is manufacturing companies listed on the Indonesia Stock Exchange for the 2021- 2023 period with sampling techniques using purposive sampling. The data analysis technique used multiple linear regression analysis to test the hypothesis using SPSS (Statistical Package for Social Science) software. The results of multiple linear regression analysis showed that profit management had no significant effect on the company's value with a significance value of 0.171 > 0.05, profitability measured using ROE had a significant positive effect on the company's value with a significance value of 0.000 < 0.05, and capital structure measured using DER had no significant effect on company value with a significance value of 0.110 > 0.05. Simultaneously, profit management, profitability, and capital structure simultaneously have a positive and significant effect on the company's value.